Pengaruh Sudut Lubang pada Sonic Crystal terhadap Atenuasi dengan Bahan Pipa PVC: Gontjang Prajitno, Catharina Risti Indriyani, Suyatno Suyatno - Gontjang Prajitno Gontjang Prajitno; Catharina Risti Indriyani Catharina Risti Indriyani; Suyatno Suyatno (Jurnal Fisika dan Aplikasinya, 2020)
In this sonic crystal research, a 1.5 " diameter and 1.1 meters long PVC pipe was used. The panel was designed to have a 3-row square configuration with a filling ratio of 0.5, several pipes are 16 for each row and each pipe was given a hole (perforation) with a radius of holes are 6 mm. The study was conducted with variations in the number of holes 2, 4, 6 and 8 holes and the direction of the angle of the sound source with holes 0, 30, 90, 150, and 1800 . optimal, where the attenuation average is -10.66 dB, while the average attenuation at 00 is -4.0 dB, at 900 is -6.7 dB, at 1500 is -4.0 dB and at an angle of 1800 of -4.4 dB. Besides, the number of holes in this study affects the attenuation of sound and shifting the frequency of resonance, the more holes in the pipe, the greater the decrease in SPL.